Efektivitas Penerapan Model Problem Based Learning Berbantuan Media Audio-Visual Terhadap Pemahaman Konsep Matematika - Nasrullah; Sukarna; Sitti Hasna (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2023)
This study aims to determine the effectiveness and comparative effectiveness of problem-based learning models assisted with audio-visual media and direct learning models in terms of understanding mathematical concepts of students of SMP Negeri 3 Sengkang. This type of study is a pseudo-experiment with an unbalanced pretest-posttest control group design. The population in this study were students of grade VIII SMP Negeri 3 Sengkang (Semester II) as many as 5 classes. Sampling using cluster random sampling techniques namely Class VIII - A and Class VIII-C involved as many as 48 people as experimental class and control class. The instruments used in this study are test instruments and non-test instruments that have been validated by mathematics education lecturers with valid and useful results. The results showed that: (1) Learning by applying problem-based learning model assisted by audio-visual media is effective in terms of understanding mathematical concepts of students with an average of studentunderstanding of the concept of problem-based learning model assisted by audio-visual media of 82.17 with a very high category and achieve classical completion of 83%, (2) Learning with direct learning model is less effective in terms of understanding mathematical concepts of students with an average understanding of the concept of students with direct learning model of 62.00 with the medium category and did not achieve a classical completion of 24%, (3) problem-based learning model assisted by audio- visual media is more effectively applied than direct learning model in terms of understanding mathematical concepts.